Fortune's runaway bride - Leigh, Allison (Fortunes of Texas. Hitting the jackpot., 2023)
Almost bride Isabel Banninger just tore out of the chapel on what should have been her wedding day. In desperate need of escape, she accepts a ride from corporate Casanova Reeve Fortune--a man she has every reason to distrust. Reeve can't explain why he offers to hide Isabel away. But as they hunker down in his family's castle, the prickly duo discovers a connection that surprises them both...